KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN MODEL TPS (THINK, PAIR, SHARE) BERBANTUAN VIDEO YOUTUBE BERMUATAN KEARIFAN LOKAL SUMATERA UTARA PADA SISWA KELAS VII - Lubis, Ilman Nafian; Ida Zulaeha; Zuliyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the instructional design for teaching descriptive writing skills using the Think Pair Share (TPS) model supplemented by YouTube videos featuring local wisdom from North Sumatra for seventh-grade students. This study employs a descriptive approach using a literature review (library research) method through the collection of data from various scientific sources, including books, journal articles, and supporting documents. The findings indicate that the implementation of the TPS model supported by featuring local wisdom of North Sumatra is capable of creating learning that is more active, collaborative, and contextual. The TPS model provides students with the opportunity to think independently, discuss, and present their ideas, while YouTube videos help students gain a concrete understanding of the objects being described. The integration of North Sumatra’s local wisdom also contributes to fostering cultural appreciation and enhancing students’ motivation to learn. Thus, the combination of the TPS model and YouTube video media based on local wisdom has the potential to improve the descriptive writing skills of seventh-grade students.